Ultrasound of the thyroid gland in the newborn: normative data. Issue 3 (1st November 2002) - Perry, R J; Hollman, A S; Wood, A M; Donaldson, M D C
Abstract : Objective: To establish reference ranges for thyroid length, breadth, depth, and volume in healthy term Scottish infants. Design: Prospective observational study of 100 (49 male) neonates. Length, breadth, and depth were measured, and the volume of each lobe was calculated using the formula for a prolate ellipsoid (volume = length × breadth × depth × π/6). Results: All measurements showed gaussian distribution, with no significant differences between the right and the left lobes. Values (mean (SD) range) were: length (cm), 1.94 (0.24) 0.9–2.5; breadth (cm), 0.88 (0.16) 0.5–1.4; depth (cm), 0.96 (0.17) 0.6–2.0; volume (ml), 0.81 (0.24) 0.3–1.7; combined volume (ml), 1.62 (0.41) 0.7–3.3. Although there was no difference in mean volume between right and left lobes, there was considerable variation (−0.8 to + 0.7 ml) between the two lobes in individual babies. Conclusions: Both lobes should be measured to give a combined volume. Our findings provide a reference against which thyroid hypoplasia or goitre can be evaluated.